2015
DOI: 10.1016/j.jconrel.2015.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Silk-based stabilization of biomacromolecules

Abstract: Silk fibroin is a high molecular weight amphiphilic protein that self-assembles into robust biomaterials with remarkable properties including stabilization of biologicals and tunable release kinetics correlated to processing conditions. Cells, antibiotics, monoclonal antibodies and peptides, among other biologics, have been encapsulated in silk using various processing approaches and material formats. The mechanistic basis for the entrapment and stabilization features, along with insights into the modulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 175 publications
(208 reference statements)
2
118
0
1
Order By: Relevance
“…Air-dried silks provide a protective barrier that physically immobilized blood components with access to minimal residual moisture, in turn conferring conformational stability (34). We directly demonstrated that the physical entrapment provided by the silk matrix was effective in mitigating thermally induced degradation and we can infer there are additional benefits such as preventing exposure to enzymatic and UV stresses (26).…”
Section: Discussionmentioning
confidence: 72%
“…Air-dried silks provide a protective barrier that physically immobilized blood components with access to minimal residual moisture, in turn conferring conformational stability (34). We directly demonstrated that the physical entrapment provided by the silk matrix was effective in mitigating thermally induced degradation and we can infer there are additional benefits such as preventing exposure to enzymatic and UV stresses (26).…”
Section: Discussionmentioning
confidence: 72%
“…Silk sponge of pore size of 400–500 ÎŒm was prepared as previously described [31]. Tubular silk sponge (2 mm inner diameter, 4 mm outer diameter, 4 mm height) were cut from the sponge with dermal punches.…”
Section: Methodsmentioning
confidence: 99%
“…Silk is an unique candidate to address these issue due to its excellent mechanical properties, biocompatibility, tunable degradability [29, 30], as well as the ability of silk to stabilize various of bioactive compounds [31]. We recently demonstrated the feasibility of silk protein as a molding and machinable biomaterial system for the preparation of devices for craniofacial repairs, based on the use of an organic solvent-based process (1,1,1,3,3,3 hexafluro-2-propanol (HFIP)) [29].…”
Section: Introductionmentioning
confidence: 99%
“…Silk fibroin (SF) has emerged as an outstanding material for biomolecule stabilization and delivery [26][27][28][29][30] . SF is biocompatible and biodegradable, eliciting minimal inflammatory response 31,32 , and has been used in medical applications including sutures and surgical mesh scaffolds 33 .…”
Section: Introductionmentioning
confidence: 99%